Interrelationship between the Alimentary Tract, Food and Feeding Habits of Plueronectiform Fishes of Southeast Coast of India - Lakshmi, S. Asta (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: This paper examines the interrelationships between the morphology of the alimentary tract, the type of food and the feeding behaviour in 22 sps. of flatfishes obtained from Cuddalore coast, Tamilnadu, India. 1051 specimens (Psettodidae-52, Bothidae-355, Pleuronectidae-37, Soleidae-364 and Cynoglossidae-243) were procured from trawls operated at a depth of 15-25 fathoms along the Cuddalore coast. To study the functional morphology of the alimentary canal of flatfishes, the nature of mouth, kind of teeth, gillrakers, number of pyloric caeca and the position of stomach, intestine and rectum were examined. Frequency of occurrence methods were employed for their stomach contents analysis. The result of the present study related to the type of food with the morphology of the alimentary tract shows flatfishes obtained from Cuddalore coast categorised into 3 groups i.e. Fish feeders (Psettodidae and Bothidae type-I), Crustacean feeders (Bothidae type-II, Pleuronectidae and Cynoglossidae) and Polychaete-Mollusc feeders (Soleidae). In Psettodidae and Bothidae type-I, the relative length of buccal cavity and stomach were much greater than in Bothidae type-II, Pleuronectidae and Cynoglossidae. However in Soleidae these two sections of the alimentary tract were less important. For the intestine the reverse was evident whereas the rectum exhibits similarity in all faltfishes. Key words: Flatfish, Plueronectiform, Feeding behaviour, Alimentary Tract --- Suganthi Devadason Marine Research Institute, Manonmaniam Sundaranar University, Tuticorin – 628 001, India --- Please Cite This Article As: S. Asta Lakshmi. 2010. Interrelationship between the Alimentary Tract, Food and Feeding Habits of Plueronectiform Fishes of Southeast Coast of India. J. Exp. Sci. 1(6):1-7.